Development of Intertextual-Based Learning Videos on The Concept of The Influence of Changes in Concentration on Shifts in Equilibrium - Putri Nisrina; Wiji Wiji; Tuszie Widhiyanti (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to produce an intertextual-based learning video on the concept of the effect of concentration on shifting equilibrium. This research uses the development research method (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The resulting product is an animated video in the form of mp4 which contains the concept of the effect of concentration on shifting equilibrium. Based on the assessment of product quality by content experts obtained a percentage of 85.71% with a very good category (VG); from the pedagogy expert assessment obtained a percentage of 90.27% with a very good category (VG); from the media expert assessment obtained a percentage of 95.60% with a very good category (VG). The video was implemented by limited testing to high school students in class XI as many as 34 students, and chemistry teachers using questionnaires, and according to the assessment of high school chemistry teachers obtained a percentage of 97.40% in the very good category (VG). This product received a positive response from students with a percentage of 90%. Based on the feedback received from experts, teachers and student responses, this learning video was revised so that it can be used as an alternative media for the chemistry learning process in the classroom.